Effect of Variable Injection Sites for Indocyanine Green Dye on the Success of Lymphaticovenular Anastomosis - Nuri, Takashi; Iwanaga, Hiroyuki; Otsuki, Yuki; Ueda, Koichi (Journal of Reconstructive Microsurgery Open, 2019)
Background Indocyanine green lymphography (ICGL) allows more accurate visualization for lymphaticovenular anastomosis (LVA). However, the protocol for ICGL has not been established yet. We investigated how injection sites of ICG affect lymphography results by comparing ICGL images based on different injection sites on the same patients.Methods Our hospital followed two ICGL protocols over time: ICG was injected into patients' 1st to 4th toe web spaces during 2013 to 2017 (Protocol 1), but into their lateral and medial ankles and 1st and 4th toe web spaces starting in 2018 (Protocol 2). Ten patients with secondary lymphedema who underwent LVA twice, using each protocol, were included in this study. We compared their results in detail and evaluated the effects of variable ICG injection sites.Results The average period between patients' first and second LVAs was 506 days. In six patients, Protocol 2 detected new and additional linear findings that had not been detected by Protocol 1. Average reduction of lower limb circumferences after second LVAs (using Protocol 2) was 2.73 cm in patients who showed new linear findings, whereas those with no new findings showed little reduction.Conclusion LVA based on ICG injections only into the dorsum of the foot can miss valuable findings. Variable ICG injection sites may improve detection of lymphatic flow and LVA efficacy.
Keywords: indocyanine green lymphography; injection site